ENHANCING THE MASTERY OF LONG SERVICE BADMINTON TECHNIQUES USING THE DRILL METHOD AMONG ELEVENTH- GRADE STUDENTS AT SMA NEGERI 1 BADAR - Safrudin Fahmi; Melfa Br Nababan; Orbit Irwansyah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This classroom action research aims to improve the mastery of long service techniques in badminton through the implementation of the drill method for eleventh-grade students at SMA Negeri 1 Badar. The study was motivated by preliminary observations indicating that a majority of students lacked proficiency in performing the long service, a fundamental skill in badminton, due to insufficient understanding of basic techniques and a lack of targeted practice. Conducted over two cycles, this collaborative research employed a systematic approach involving planning, action, observation, and reflection. Data were collected through practical skill tests and direct observation, using a structured assessment rubric, and were analyzed quantitatively using descriptive statistics. The results demonstrated a significant improvement in student performance. In the pre-action phase, only 24.24% of students (8 out of 33) achieved the "good" category. After the first cycle, this figure rose to 48.48%. By the conclusion of the second cycle, 90.91% of students (30 out of 33) had reached the "good" and "very good" categories. The findings conclusively indicate that the systematic and repetitive nature of the drill method effectively enhances motor skill acquisition and technical proficiency in the badminton long service. This study recommends that Physical Education (PE) teachers incorporate the drill method into their teaching strategies for racquet sports and other skill-based physical activities.